Medium-dose riboflavin as a prophylactic agent in children with migraine: A preliminary placebo-controlled, randomised, double-blind, cross-over trial - Bruijn, Jacques; Duivenvoorden, Hugo; Passchier, Jan; Locher, Heiko; Dijkstra, Natascha; Arts, Willem-Frans (Cephalalgia, 2010)
Background: Riboflavin seems to have a promising effect on migraine in adults. The present study examines whether riboflavin has a prophylactic effect on migraine in children. Objective: To investigate whether riboflavin in a dosage of 50 mg/day has a prophylactic effect on migraine attacks in young children. Subjects and methods: This randomised, placebo-controlled, double-blind, cross-over trial included 42 children (aged 6–13 years) with migraine of whom 14 children were also suffering from tension-type headache. Following a 4-week baseline period, all children received placebo for 16 weeks then riboflavin for 16 weeks (or vice versa) with a washout period of 4 weeks in between. The primary outcome measure was reduction in mean frequency of migraine attacks and tension-type headache in the last 4 weeks at the end of the riboflavin and placebo phase, compared with the preceding baseline or wash-out period. Secondary outcome measures were mean severity and mean duration of migraine and tension-type headaches in the last 4 weeks at the end of the riboflavin and placebo phase, compared with the preceding baseline or wash-out period. Results: No significant difference in the reduction of mean frequency of migraine attacks in the last month of treatment was found between placebo and riboflavin (P = 0.44). However, a significant difference in reduction of mean frequency of headaches with a tension-type phenotype was found in favour of the riboflavin treatment (P = 0.04). Conclusions: In this group of children with migraine, there is no evidence that 50 mg riboflavin has a prophylactic effect on migraine attacks. We found some evidence that 50 mg riboflavin may have a prophylactic effect on interval headaches that may correspond to mild migraine attacks or tension-type headache attacks in children with migraine.